Decolonizing Sovereignty: States of Exception along the Kenya-Somali Frontier. Issue 1 (4th February 2019) - MacArthur, Julie
Abstract: During the "long moment" of decolonization, a central tension emerged between a conception of sovereignty in territory and sovereignty in bodies, of international standards of statehood and popular notions of self-determination. The borderland between Kenya and Somalia has long acted as a flashpoint for broader debates over belonging, security, and territoriality. Throughout the twentieth century, Somali partisans variously resisted, negotiated, and confounded frontier governance and became the alien "strangers" in colonial Kenya's racial order. While supporters of a "Greater Somalia" reworked internally diverse practices of mobility and kinship into a rhetoric of self-determination and trans-territorial statehood, Kenyan nationalists secured their own postcolonial inheritance by transforming Kenya's northern frontier into the core of often violent performances of state power. The conflict over Kenya's northern frontier in the 1960s was a battle not over territory or material resources, but over the very meaning of sovereignty, citizenship, and nationalism. As spaces of both resource and refuge, exception and precarity, borderlands provide a particularly productive lens through which to examine the decolonization of sovereignty. Neither peripheral nor exceptional, foregrounding colonial borderlands requires analytical and methodological shifts that challenge the uncritical dichotomy between territorial fixity and mobility, historicize the discursive and practical content of sovereignty, and contribute to larger debates over the continuing global processes of decolonization.